Design and Implementation of a Microcontroller-Based Automatic Floor Mopping Robot - Elbiem Kusuma (Indonesian Journal of Electronics and Computer Technology, 2026)
The development of an automatic floor-cleaning robot provides an innovative solution for addressing water puddles that frequently accumulate after rainfall. Although such puddles may appear insignificant, they can pose serious safety risks by increasing the likelihood of slip-and-fall accidents, particularly in public facilities such as mosques. This study presents the design and implementation of an ESP32-based automatic floor mopping robot intended to assist mosque caretakers (marbot) in maintaining floor cleanliness more efficiently and with reduced physical effort. The system was developed using the Software Development Life Cycle methodology with the Waterfall model, which consists of four sequential stages: planning, analysis, design, and implementation. The proposed robot integrates hardware and software components to perform automated floor-cleaning operations and can be controlled through a mobile application. System testing was conducted to evaluate functionality, reliability, and operational performance, as well as to verify that the developed system operated without significant errors and fulfilled the intended design objectives. The testing results demonstrated that the robot was capable of effectively mopping mosque floors, reducing the workload of mosque caretakers, and providing a practical and efficient cleaning solution. Consequently, the proposed system has the potential to improve both cleanliness management and user safety within mosque environments.